Perbandingan Kinerja Keuangan Pemerintah Daerah Antara Pemerintah Kabupaten dan Pemerintah Kota (Studi Kasus Pada Kabupaten/Kota Di Pulau Sumatera Tahun 2015-2019) - Rifdah Qurratunnisa; Ratna Septiyanti; Usep Syaipudin; Fitra Dharma (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The difference in financial performance between district and city governments is one of the example of high economic gap. This is due to differences in the size of an area, population density levels and different regional income which can lead to fiscal imbalances between regions. The purpose of this study is to compare the financial performance of district and municipal administrations on Sumatra Island from 2015 to 2019. This study used financial statement data for all district and city governments on the island of Sumatra and analyzed the differences using descriptive statistic methods with quantitative data analysis technique using the Mann Whitney Test. The Mann Whitney Test results revealed that there were significant differences in the ratios of independence, efficiency, operating expenditure, capital expenditure, and the degree of fiscal decentralization, but no significant differences in the effectiveness ratio between district and city governments.